2022
DOI: 10.5603/fm.a2020.0103
|View full text |Cite
|
Sign up to set email alerts
|

Topography of the common fibular nerve terminal division in human foetuses

Abstract: Background:The progress of pediatric surgery and increasingly better diagnosis of fetal defects require detailed knowledge of human developmental anatomy. Precise knowledge of the anatomy of innervation of the lower extremities corresponds to this subject and is not only cognitive but also clinically important. The end of the common fibular nerve is superficially located in the area exposed to frequent injuries as well as in the area subject to possible surgical repair procedures. Materials and methods:The ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…In the reviewed literature, most authors have reported that CPNe occurs around the fibular head and neck [ 1 , 3 , 9 12 ]. In the human fetuses, the terminal branch of CPN was based on the head of the fibula: (i) high cleavage-above the head of the fibula (1%), (ii) median cleavage-fibula head height (34%), and (iii) low cleavage-below the fibula head (65%) [ 22 ]. Also, CPN is superficial in the subcutaneous space directly over the unyielding fibula and is tethered by tight fascial bands.…”
Section: Discussionmentioning
confidence: 99%
“…In the reviewed literature, most authors have reported that CPNe occurs around the fibular head and neck [ 1 , 3 , 9 12 ]. In the human fetuses, the terminal branch of CPN was based on the head of the fibula: (i) high cleavage-above the head of the fibula (1%), (ii) median cleavage-fibula head height (34%), and (iii) low cleavage-below the fibula head (65%) [ 22 ]. Also, CPN is superficial in the subcutaneous space directly over the unyielding fibula and is tethered by tight fascial bands.…”
Section: Discussionmentioning
confidence: 99%
“…-Estágio I: Hipoestesia tátil -Estágio II: Alodínia mecânica simples -Estágio III: Neuralgia intermitente -Estágio IV: Neuralgia permanente -Estágio V: Síndrome da Dor Regional Complexa de Budapest A maioria dos pacientes com sintomas de dor neuropática é tratada na atenção primária, com apenas uma minoria sendo encaminhada para avaliação e diagnóstico clínico especializado. Muitos pacientes que apresentam dor neuropática têm sintomas nos membros inferiores, em especial na região femoral, devido à sua localização anatômica (Nobel et al, 1980;Jakubowicz, 1991;Kargel et al, 2006). No entanto, quando tratamos de lesões periféricas, é importante considerarmos os domínios que representam os territórios de onde emanam os nervos, ou seja, um conjunto de terminações nervosas sensitivas cujos axônios carregam uma sensibilidade comum (Spicher et al, 2020b).…”
Section: Conclusãounclassified
“…• Sensory function: the anterolateral surface of the shin and dorsum of the foot (deep branch innervates space between first and second toes) (Anderson, 2016;Capodici et al, 2022;De Maeseneer et al, 2015;Karykowska et al, 2022;Poage et al, 2016).…”
Section: Anatomy Of the Common Fibular Nerve (Cfn) And Fabella-induce...mentioning
confidence: 99%
“…After that, it arrives at the lateral compartment of the leg, where it divides into deep and superficial branches. The CFN is a sensory‐motor nerve: Motor function: dorsiflexion of the foot, toe extension, ankle eversion; thus, palsy causes foot drop; Sensory function: the anterolateral surface of the shin and dorsum of the foot (deep branch innervates space between first and second toes) (Anderson, 2016; Capodici et al, 2022; De Maeseneer et al, 2015; Karykowska et al, 2022; Poage et al, 2016). …”
Section: Anatomy Of the Common Fibular Nerve (Cfn) And Fabella‐induce...mentioning
confidence: 99%
See 1 more Smart Citation